Neutrophil Extracellular Traps Regulate HMGB1 Translocation and Kupffer Cell M1 Polarization During Acute Liver Transplantation Rejection - Liu, Yanyao; Pu, Xingyu; Qin, Xiaoyan; Gong, Junhua; Huang, Zuotian; Luo, Yunhai; Mou, Tong; Zhou, Baoyong; Shen, Ai; Wu, Zhongjun (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) play important roles in hepatic ischemic reperfusion injury (IRI) and acute rejection (AR)-induced immune responses to inflammation. After liver transplantation, HMGB1, an inflammatory mediator, contributes to the development of AR. Even though studies have found that HMGB1 can promote NET formation, the correlation between NETs and HMGB1 in the development of AR following liver transplantation has not been elucidated. In this study, levels of serum NETs were significantly elevated in patients after liver transplantation. Moreover, we found that circulating levels of NETs were negatively correlated with liver function. In addition, liver transplantation and elevated extracellular HMGB1 promoted NET formation. The HMGB1/TLR-4/MAPK signaling pathway, which is initiated by HMGB1, participates in NET processes. Moreover, in the liver, Kupffer cells were found to be the main cells secreting HMGB1. NETs induced Kupffer cell M1 polarization and decreased the intracellular translocation of HMGB1 by inhibiting DNase-1. Additionally, co-treatment with TAK-242 (a TLR-4 inhibitor) and rapamycin more effectively alleviated the damaging effects of AR following liver transplantation than either drug alone.